CLINICAL AND LASERFLUORESCENCE STUDY REGARDING PREVALENCE OF INCIPIENT OCCLUSAL CARIES TO PATIENTS WITH DIFFERENT CARIOGENIC RISKS CATEGORIES - Topoliceanu Claudiu; Iovan Gianina; Ghiorghe Angela; Stoleriu Simona; Pancu Galina; Georgescu Andrei; Andrian Sorin (Romanian Society of Oral Rehabilitation, 2014)
The study aimed to determine prevalence of incipient occlusal caries related to different cariogenic risk categories as well as the distribution of incipient occlusal caries accordingly to ICDAS classification and results of laserfluorescence examen. Material and methods. The study group included patients classified in low cariogenic risk (18 patients, 320 occlusal surfaces), medium cariogenic risk (65 patients, 320 occlusal surfaces) and high cariogenic risk (32 patients, 527 occlusal surfaces). 1960 occlusal surfaces were assessed using clinical examen (ICDAS system) and laserfluorescence method (DIAGNODENT, Kavo). Results. For the category of low cariogenic risk patients, most incipient occlusal caries are classified as code ICDAS 02 (11.56%) and 13.43% are recorded in the range of values 10-20 (enamel caries) accordingly to laserfluorescence examen. The patients with medium cariogenic risk present similar rates of incipient occlusal caries with codes ICDAS 02 (13,74%) and 03 (13,56%), as well as 20,20% occlusal surfaces recorded with values 10-20 in laserfluorescence method. The patients with high cariogenic risk present similar rates of incipient occlusal caries with codes ICDAS 02 (15,55%) and 03 (13,66%), as well as 18,78% occlusal surfaces recorded with values 10-20 (enamel caries) and 14,23% (dentinal caries) with values over 30, in laserfluorescence method. Conclusions. The rates of incipient occlusal caries, accordingly to ICDAS system and laserfluorescence examen, are also influenced by cariogenic risk category.